Determination of digestible lysine and estimation of essential amino acid requirements for bullfrogs - Mansano, Cleber Fernando M. [UNESP]; Macente, Beatrice Ingrid [UNESP]; Nascimento, Thiago Matias T. [UNESP]; Pereira, Marcelo M.; da Silva, Edney P. [UNESP]; De Stéfani, Marta V. [UNESP] (Elsevier, 2017)
The traditional method to determine the nutritional requirements of animals is based on individual dose–response experiments that are time consuming and costly. One alternative to establish the dietary protein profile is the use of the ideal ratio between essential amino acids and digestible lysine to estimate essential amino acid requirements. The objective of this study was to determine the digestible lysine requirement of bullfrogs and to estimate essential amino acid requirements based on the ideal ratio. The experimental design was completely randomized and consisted of five treatments and three replicates. Six hundred froglets with an initial mean weight of 51.53 ± 1.91 g, identified through an implanted transponder, were used. The experimental diet (30.42% digestible protein) was supplemented with five levels of lysine HCl (0, 0.7, 1.4, 2.1, and 2.8%), so that the diets contained 1.38, 2.11, 2.85, 3.65 and 4.39% digestible lysine. The performance variables were feed intake, weight gain, feed conversion, specific growth rate, protein efficiency ratio, protein retention efficiency, and body protein and lysine deposition. The optimum level of digestible lysine was obtained at the intersection of the ascending line with the response plateau. Weight gain increased until reaching 222.7 g at 2.23% digestible lysine in the diet. The best feed conversion (1.4 g/g) and body protein (48.28 g) and lysine (4.07 g) deposition were observed at 2.29%, 2.33% and 2.39% digestible lysine, respectively. The digestible lysine requirement of bullfrogs is 2.71% of dry weight or 8.91% of dietary digestible protein, a level that provides the highest protein retention efficiency. The requirements of the other digestible amino acids estimated based on the concept of the ideal ratio of essential amino acids are (of dry weight): 2.16% arginine; 0.94% histidine; 1.34% isoleucine, 2.39% leucine; 0.79% methionine; 1.31% phenylalanine; 1.34% threonine; 0.23% tryptophan; 1.58% valine; 0.36% cystine, and 1.07% tyrosine. Statement of Relevance The estimate requirement of digestible essential amino acid using the concept of the ideal ratio permits the elaboration of diets with an appropriate amino acid, maximizing growth, protein utilization efficiency and carcass quality for bullfrogs.
Keywords: Amino acid profile; Broken-line; Lysine; Nutritional requirement